CANIS LUPUS (MAMMALIA, CANIDAE) FROM THE LATE PLEISTOCENE DEPOSIT OF AVETRANA (TARANTO, SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Here we described the remains of Canis lupus from the bed 8 of Avetrana karst filling (Late Pleistocene; Taranto, Southern Italy). The studied specimens are larger than those collected from the early Late Pleistocene Apulian localities and those referred to the recent Italian wolf. Moreover, the remains from Avetrana are morphometrically close to Canis lupus maximus from France and to C. lupus collected from Central and Northern Italian localities, chronologically related to MIS 2 and MIS 3. Morphologically, the studied specimens slightly differ from both C. l. maximus and other Pleistocene Apulian wolves. The dimensional differences between the Avetrana wolves and those collected from the other early Late Pleistocene Apulian localities could be explained through a spread of a large-sized morphotype from the Northern Italy.